Your heart can`t see what sneakers you are wearing: Exercise training load in endurance athletes is inadequately quantified in sports cardiology - Dausin, C.; Tironi, R. M.; Cornelissen, V.; Hespel, P.; Willems, R.; Haykowsky, M.; La Gerche, A.; Claessen, G.; Foulkes, S. (Canadian Journal of Cardiology, 2024)
Background Training load may be an important factor underlying the (patho-)physiologic cardiovascular adaptations from endurance exercise. Yet, quantifying training load remains challenging due to the complexity of its components (Frequency, Intensity, Time, and Type [FITT]). In this systematic review we evaluate how training load has been quantified in sports cardiology studies and provide recommendations for how this can be improved.